Detection of Adrenaline Based on Substrate Recycling Amplification. (2015) - Molinnus, D.; Bartz, A.; Bäcker, M.; Siegert, P.; Willenberg, H.; Poghossian, A.; Keusgen, M.; Schöning, M.J.
Abstract: An amperometric enzyme biosensor has been applied for the detection of adrenaline. The adrenaline biosensor has been prepared by modification of an oxygen electrode with the enzyme laccase that operates at a broad pH range between pH 3.5 to pH 8. The enzyme molecules were immobilized via cross-linking with glutaraldehyde. The sensitivity of the developed adrenaline biosensor in different pH buffer solutions has been studied.